Facial Recognition in Asylum Seeker Procedures: Criminal Implications of Data Misuse and Profiling - Anggriawan, Rizaldy; Hamsin, Muhammad Khaeruddin; Karsai, Krisztina; He, Yizhou (Jurnal Media Hukum, 2026)
The current use of facial recognition technology (FRT) for asylum-seeker provides a more reliable method of establishing identity than previous methods; however, FRT also raises broader concerns about individual rights to privacy, data security, and algorithmic bias. This study aims to identify opportunities for criminal law to address these concerns by reviewing existing legal and regulatory frameworks in the European Union (GDPR/EU), the United States (BIPA), Brazil (LGPD), Australia (Privacy Act 1988), and International Refugee Legal Instruments. Using doctrinal legal methods, this study evaluates current statutory law, case law, and academic literature on biometric data in the context of the asylum process. The research identified several major challenges posed by the application of FRT, including unlawful data collection, excessive monitoring of individuals, racial profiling, identification errors, and function creep, all of which may expose individuals to criminal liability across multiple jurisdictions. Based on these findings, it is recommended that greater assurance of protection be provided through statutory law, enhanced accountability, and independent oversight of FRT's application to the asylum process to ensure compliance with established human rights principles.